Learning Outcomes, Methodological Indications For Their Conception, Definition, And Implementation In Engineering Programs Based On The ABET/EUR-ACE® Principles And Criteria (Journal of Namibian Studies : History Politics Culture, 2023)
This article proposes a theoretical and methodological alternative for the conception, definition, and implementation of learning outcomes (LOs) in engineering programs based on ABET/EUR-ACE® principles and criteria. From a socio-critical approach, the identification, definition, organization, and systematization of a set of theoretical categories associated with the incorporation of LOs in the teaching learning processes (TLPs) in professional engineering training programs is highlighted, based on the guidelines and principles of the different accreditation bodies worldwide. A theoretical and methodological approach is presented of the different conceptions, principles, and criteria valued as relevant in the process of defining LOs and their relation with engineering TLPs based on a didactic structure with a system character that streamlines the process of articulation of LOs with the educational objectives of said academic programs. A theoretical and methodological proposal shaped in practice is presented from an institutional experience based on ABET criteria.